Ecological dimensions of the family: the children' s social situation - Tessier, Réjean (1994)
This article is abour the social siruation of the families and their children. The author uses rbe ecological paradigm whicb undersrands behavior as the result of a mutual and reciprocal exchange between tbe organism and the environment. Using statistical data from the WHO and UNICEF, he tries to demonstrare the possible consequences of certain social situations and the demografic contex on the oportunities of children's development. The different levels of ecological dimensions of the family are described and the negative effects of poverty and adverse family conditions are pointed out.